Knowledge, attitude, and practices towards hepatitis infection and its associated factors among adults in Gondar town, northwest Ethiopia; a community-based study, 2021 - Abiy Ayele Angelo; Bisrat Birke Teketelew; Dereje Mengesha Berta; Elias Chane; Negesse Cherie; Mesele Nigus; Getu Girmay; Mebratu Tamir; Mehari Bitew (BMC, 2024)
Abstract Background Hepatitis virus infection remains a serious public health concern worldwide. Percutaneous, mucosal, or non-intact skin exposure to infectious blood, semen, and other body fluids are the major routes of infection in endemic areas, including Ethiopia, where little is known about the community's knowledge, attitudes, and practice toward hepatitis infection. Thus, this study aimed to determine the knowledge, attitude, and practices towards hepatitis infection among adults in Gondar town. Methods A community-based cross-sectional study was conducted from July to August 2021 on a total of 390 participants. Proportional sample allocation was used in 3 randomly selected sub-cities. Then, study participants from randomly selected households were recruited by using a systematic random sampling technique. Socio-demographic data and questions regarding KAP were collected via a self-administered and interviewer-administered questionnaire. Statistical analysis was performed using SPSS version 20. Logistic regression analyses were used to identify the associated factors and a p-value < 0.05 was considered statistically significant. Results The mean age of the study participants was 30 ± 8.43 years and more than half ½ (53.3%) ranged from 26 to 40 years old. In this study, 335 (85.9%) of study participants had poor knowledge about hepatitis infection. About 344 (88.2%) had a negative attitude toward hepatitis infections, and 344 (88.2%) of the participants had a poor practice to prevent hepatitis infections. Multivariate analysis affirmed that having vaccination for hepatitis infection was significantly associated with a positive attitude (AOR, with 95% CI: 2.135 (1.006-4.532) and good practice levels (AOR, with 95% CI: 22.623 (0.032-0.156). Conclusions and recommendations In this study majority of the participants have poor knowledge, attitudes, and practices toward hepatitis infection. Therefore, targeted community-based interventions are necessary. However, this study revealed that having vaccination for hepatitis infection was significantly associated with a positive attitude and good practice levels among the study participants.